Subdiffraction Limited Photonic Funneling of Light. Issue 24 (21st October 2020) - Li, Kun; Simmons, Evan; Briggs, Andrew; Nordin, Leland; Xu, Jiaming; Podolskiy, Viktor; Wasserman, Daniel
Abstract: Efficient optical coupling between nano‐ and macroscale areas is strongly suppressed by the diffraction limit. This work presents a possible solution to this fundamental problem via the experimental fabrication, characterization, and comprehensive theoretical analysis of structures referred to as "photonic funnels." The funnels represent a novel composite material platform that combines hyperbolic dielectric response with geometry‐assisted optical confinement. Experimentally, funneling of mid‐infrared light through openings with diameters as small as 1/25th of the free space wavelength (λ0 ) is demonstrated. By analyzing the optical response of the funnels, as fabricated, both confinement of mid‐infrared radiation to the λ0 /25 areas and efficient outcoupling of light from deep subwavelength areas are confirmed. Abstract : A novel material platform offering efficient coupling between free‐space and deep‐subwavelength features, photonic funnels, is presented. Efficient transmission of infrared (IR) light through the funnels is shown, both experimentally and theoretically. The funnels are numerically demonstrated to enable efficient outcoupling of mid‐IR light from nanoscale features, offering a practical avenue for interfacing between the nano‐ and macroworlds.